A posição do narrador no romance Ao farol, de Virgínia Woolf - Cherpinski, Adriane (2020)
When it appeared, the novel occupied the space of a literature that no longer fit the human at that moment, the epic. From the moment that man becomes disenchanted with life, he begins to look for an art that fits his new way of feeling the world. After a brief history of the genre, presenting the author and the work, this article focuses on analyzing the narrator's position in the novel To the lighthouse (1927), by writer Virginia Woolf, according to the essay "The position of the narrator in the novel contemporary "written by the philosopher Theodor W. Adorno. It is public knowledge that Woolf's work was considered innovative by critics. In this perspective, we sought to investigate which features make the novel To the lighthouse so considered, and if such points align it to what Adorno calls contemporary romance.